2013
DOI: 10.5539/jas.v5n3p45
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency of Dairy Farms: A Stochastic Frontier Application on Dairy Farms in Jordan

Abstract: The present study was conducted to determine the level of technical efficiency of dairy producing farms in Jordan by applying the stochastic production frontier (SPF) methodology. Technical efficiency estimates were generated for 100 dairy farms in Jordan. The results of the study indicated that technical efficiency of milk production by most of dairy farms in Jordan is low. The mean technical efficiency was estimated to be only 39.5% for the sampled dairy farms. This means that an average farm in the sample c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…It denotes that herd size had an inverse relationship with farming efficiency, which means that the increase of herd size, will reduce the efficiency of dairy farms. This result conversely with the results of studies by Demircan et al (2010) and Al-Sharafat (2013). The possible explanation for this result was the composition of herd consist of more nonlactating cows than lactating cows.…”
Section: Determinant Factors Of Technical Efficiency Of Dairy Farmingsupporting
confidence: 82%
“…It denotes that herd size had an inverse relationship with farming efficiency, which means that the increase of herd size, will reduce the efficiency of dairy farms. This result conversely with the results of studies by Demircan et al (2010) and Al-Sharafat (2013). The possible explanation for this result was the composition of herd consist of more nonlactating cows than lactating cows.…”
Section: Determinant Factors Of Technical Efficiency Of Dairy Farmingsupporting
confidence: 82%
“…Rural milk producers need to be able to read labels on veterinary drugs especially expiry dates. Several studies have observed a statistically significant and positive relationship between education and efficiency [23]- [27]. Education level therefore, was expected to have a positive effect on technical efficiency of milk producers though it may not do much to affect technical efficiency because majority of milk producers in cattle corridor receive practical skills on cattle operations and management from childhood.…”
Section: Factors That Influence Technical Efficiencymentioning
confidence: 99%
“…According to Ali Al-Sharafat (2013) Number of cows, feed intake and labor man days affect level of output of milk production positively while value of veterinary services, fixed inputs and depreciation costs have no significant impact on level of output of milk production. Education, herd size (cows) and experience affects efficiency in milk production positively while contact with extension service does not affect efficiency in milk production.…”
Section: Introductionmentioning
confidence: 99%
“…It means that some literatures reported some factors which affect output level and technical efficiency level of dairy farmer households either positively or negatively while others reported the same variables to have no impact on output level and efficiency level of dairy farmer households. For instance, as of Ali Al-Sharafat (2013), Bardhan and Sharma (2013) and Adane et al., (2015) veterinary cost has no impact, but positive impact as of Nega and Simeon (2006) on amount of milk produced. Labor input has positive impact on amount of milk produced as found in Ali Al-Sharafat (2013) and Adane et al.…”
Section: Introductionmentioning
confidence: 99%